Rescuenet: An Integrated Emergency Coordination And Alert System - P. Shilpasri, P. Shilpasri; C.Mounika, C.Mounika; Akella, Pravalika; N.Shreya, N.Shreya; Nandini, M.Deekshitha; Yadav, P. Krushi (Journal of Neonatal Surgery, 2025)
The disaster response suffers from delayed responses when rescue agencies fail to coordinate appropriately. The main responsibility of RescueNet consists of establishing unified connections between emergency response organizations. Real-time location monitoring capabilities combined with communication features belong to RescueNet to enable several rescue organizations to work together effectively. Users accessing the website find posted details from agencies that show their locations and contacts along with their available resources. RescueNet map functions rely on GPS Technology to show registered agency positions though real-time visual display resulting in better emergency response coordination. This website enables agencies to work together efficiently through emergency response coordination by fixing communication problems that appear in crisis situations. RescueNet functions to protect human existence while minimizing the impacts of emergencies.